Green manuring for optimal yield and soil health management under changing climate - Hasanain, Mohammad; Kumar, Sandeep; Verma, Gaurav; Meena, Vijay Singh; Meena, Sunita Kumari; Singh, Vinod Kumar (Indian Farming, 2024)
Amid concerns for soil health and fertility due to intensive agriculture and improper fertilization practices, green manuring emerges as a promising solution. By incorporating green plant material, it enriches soil with organic matter and nutrients, addressing erosion and nutrient depletion. Green manure crops suppress weeds, reduce herbicide use, and aid pest management without synthetic pesticides. Enhancing nutrient cycling, it sustains soil fertility, reducing reliance on synthetic fertilizers and offering cost savings. Crucially, it bolsters agricultural resilience to climate change, buffering against extreme weather. Green manuring presents a sustainable, cost-effective approach, balancing high yields with soil and environmental health, essential for resilient, eco-conscious farming and long-term global food security.